Deviation Of Marriage Age Issues in Indonesia (Integration Review of Maqashid Sharia and Positive Law) - Nurul Aini Octavia; Wardatun Nabilah; Martia Lestari (Istinbath : Jurnal Hukum, 2023)
This research will answer two research questions, first: what are the rules regarding marriage dispensation in Indonesia and secondly, how is the problem of "marriage age deviation" based on the principle of fulfilling the principle of the best interests of the child and the urgent reasons for requesting marriage dispensation in the Religious Courts in terms of positive law and Islamic law (maqashid syariah). This application is submitted in a child marriage which is a marriage carried out at the age of a child. A child is someone who is not yet 18 (eighteen) years old, including children who are still in the womb. This application is submitted by the applicant's parents (the bride and groom are under 19 years old). This study has not been discussed in terms of marriage age deviation. With qualitative research methods and data collection from the literature, the study shows that the existence of rules for implementing marriage age deviations causes the marriage dispensation option to give rise to new problems that have not been clearly and explicitly regulated in marriage regulations or child protection laws in Indonesia. From the perspective of maqashid sharia, this problem is not in accordance with maqashid khamsah, especially hifz al-nafs and hifz al-nasl.